2014
DOI: 10.1007/s11060-014-1416-3
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor expression is associated with improved overall survival in human glioblastoma multiforme

Abstract: Vitamin D and its analogs have been shown to display anti-proliferative effects in a wide variety of cancer types including glioblastoma multiforme (GBM). These anticancer effects are mediated by its active metabolite, 1α, 25-dihydroxyvitamin D3 (calcitriol) acting mainly through vitamin D receptor (VDR) signaling. In addition to its involvement in calcitriol action, VDR has also been demonstrated to be useful as a prognostic factor for some types of cancer. However, to our knowledge, there are no studies eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 50 publications
2
38
1
Order By: Relevance
“…Previous studies reported expression of VDR in T98G cells [21,26]. To confirm that significant expression could be detected in our cell cultures, we carried out RT-PCR with human kidney as positive control.…”
Section: Vdr Expression In the T98g Cell Linesupporting
confidence: 63%
“…Previous studies reported expression of VDR in T98G cells [21,26]. To confirm that significant expression could be detected in our cell cultures, we carried out RT-PCR with human kidney as positive control.…”
Section: Vdr Expression In the T98g Cell Linesupporting
confidence: 63%
“…In a recent study of human glioma tissue microarrays, the vitamin D receptor was found to be more highly expressed in tumor compared to nonmalignant brain tissues and expression of this receptor was associated with improved outcomes [62]. In this same study, pharmacologic modulation of these receptors in glioma cell lines altered cellular migration.…”
Section: Treatmentmentioning
confidence: 84%
“…Of note, vitamin D can induce HR expression in keratinocytes, but it is unknown if this transcriptional program is intact in GBM . Nonetheless, vitamin D has been shown to antagonize GBM growth in vitro and in vivo, and VDR protein expression has been demonstrated to be a prognostic factor in GBM . Future studies are warranted to confirm the value of vitamin D–based therapy in GBM and ascertain whether its efficacy can be attributed to upregulation of HR expression.…”
Section: Discussionmentioning
confidence: 99%